Genetic diversity of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) populations and presence of the B biotype and a nonB biotype that can induce silverleaf symptoms in quash, in Uganda - Sseruwagi, P.; Legg, James P.; Maruthi, M.; Colvin, J.; Rey, M.; Brown, J. (Wiley, 2005)
The extent of genetic variability and host-plant distribution of Bemisia tabaci (Gennadius) genotypes colonising cultivated and uncultivated plant species occurring adjacent to cassava fields in selected cassava-producing areas of Uganda in 2003/04 were investigated using the mitochondrial cytochrome oxidase I (mtCOI) gene as the molecular marker. Eight genotype clusters, Ug1–Ug8, which are supported by high bootstrap values (≥80), at 3–18% nt divergence, were revealed among the collective Ugandan B. tabaci populations. Ug1 and Ug2 (both cassava-associated) and Ug8 (sweetpotato-associated) have been reported previously in Uganda. Ug3 was genetically dissimilar to B. tabaci described elsewhere and colonised a single species, Ocimum gratissimum. Ug4–Ug7 formed four closely related subclusters (93–97% nt identity) and diverged by 15–18% from Ug1, Ug2, Ug3 and Ug8, respectively. Ug4 had as its closest relatives (at 97–99% nt identity) the Ivory Coast okra biotype, whereas genotypes Ug5 and Ug6 had as their closest relatives (at 95–99% and 99% nt identity, respectively) the Mediterranean–North Africa–Middle East (MED-NAFR-ME) biotypes, which also include the well-studied B and Q biotypes. Ug7 was closely related (at 98–99% nt identity) to biotype Ms from the Reunion Island in the Indian Ocean. Ug4 colonised Cucurbita pepo, Cucurbita sativus, Leonotis nepetifolia and Pavonia urens, while Ug7 colonised Commelina benghalensis, Gossypium hirsutum and Phaseolus vulgaris. Ug6, the B-biotype-like genotype colonised Abelmoschus esculentus and C. benghalensis only. None of Ug4–Ug7 genotypes was found associated with, or colonising, cassava or sweetpotato plants. In addition to colonising sweetpotato, the Ug8 genotypes colonised Lycopersicon esculentum and L. nepetifolia. Ug6 and Ug7, both members of the B biotype/B-like cluster, induced silverleaf symptoms on Cucurbita sp. The discovery of five previously identified B. tabaci genotype clusters, Ug3–Ug7, in Uganda, among which are some of the world's most economically important biotypes, namely B and Q, is particularly significant in the spread of geminiviruses with devastating effects to crop production in Africa.